THE ALGORITHM OF PIECEWISE CONSTANT TELEMETRIC PARAMETERS SEGMENTATION - Vitol A.D.; Zhukova N.A.; Tristanov A.B. (Vestnik KRAUNC: Fiziko-Matematičeskie Nauki, 2010)
This paper is devoted to the modification of optimal segmentation algorithm and using it to telemetric signals processing